ChemInform Abstract: Catalytic Asymmetric Synthesis of Cyclic Ethers Containing an α‐Tetrasubstituted Stereocenter. Issue 38 (30th August 2013) - Cox, Nick; Uehling, Mycah R.; Haelsig, Karl T.; Lalic, Gojko
Abstract An exo‐selective cyclization of enantioenriched trisubstituted allenes is developed in the presence of combined Au/Ag catalyst which allows the asymmetric preparation of cyclic ethers containing a tetrasubstituted stereocenter.